The study of the aerodynamic coefficients of rotating cylinders - Tanasheva, N.K.; Dyusembaeva, A.N.; Nussupbekov, B.R.; Min’kov, L.L.; Nurgalieva, Zh.G.; Sadenova, K.K. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the course of the research, the theoretical knowledge on the aerodynamic characteristics of coiled cylinders in rotary motion was reviewed and the cylinders in circular motion on the working part of the aerodynamic pipe were studied. During the studying the dependence of the aerodynamic characteristics of rotating motion cylinders on the distance change, several cases of rotation of the cylinders were considered. When the direction of rotation of the cylinders changes, it is determined that frictional coefficient and the lifting force coefficient are changed. At the same time, the distance at which the aerodynamic parameters will have the highest value is determined. The rotation of rotating moving cylinders is determined by the aerodynamic pumps of the cylinders in the horizontal direction of the airflow due to the air velocity, the number of cylinders and the distance between the two cylinders. An increase in the velocity of the airflow is determined by the reduction of the coefficient of the friction coefficient and the lifting force of the cylinders in rotary motion; The aerodynamic characteristics of the coiled cylinders were first detected to increase the distance between the cylinders and reach them at a later distance. The aerodynamic characteristics of the cylinders with diameters 10 cm in diameter, that is the rotary motion, is determined by the maximum value with the coefficient of lifting force and the frontal impedance coefficient. These results are useful for us in practice, as these results can be used in smaller wind speed engines. In the local economy, the use of local wind power is a convenient, affordable, and environmentally friendly, with a minimal wind speed engine focused on reducing the deficit of electricity, which is one of the key issues in rural areas.
Айналмалы қозғалыстағы цилиндрлердің аэродинамикалық коэффициенттерін зерттеу
Исследование аэродинамических коэффициентов вращающихся цилиндров
Keywords: rotary cylinders; magnus effect; angular barrier and lifting coefficients; Reynolds number